P679 Neisseria gonorrhoeae (GC) culture positivity by indication for culture and anatomic site, seattle, washington, 2017–2018. (14th July 2019) - Thibault, Christina; Soge, Olusegun; Kerani, Roxanne; Golden, Matthew; Barbee, Lindley
Abstract : Background: In order to increase the number of gonococcal isolates available for antimicrobial susceptibility surveillance, we expanded indications for GC culture in a municipal STD clinic in Seattle, Washington. We evaluated GC culture positivity by clinical criteria. Methods: In 2017–2018, GC culture specimens were collected from STD clinic patients who met these criteria: (1) contact to GC, (2) GC NAAT+ not yet treated, or (3) symptomatic urethritis/cervicitis with intracellular diplococci on gram stain. Clinicians inoculated Modified Thayer-Martin agar plates at the bedside and incubated in a candle jar. Patient characteristics and indication for culture were abstracted from medical records; culture positivity was compared by indication, anatomic site, and patient group with Fisher's exact test. Results: Clinicians collected a total of 3, 884 specimens, of which 1, 107 (29%) were GC culture positive. Culture positivity among 74 endocervical, 1, 611 pharyngeal, 1, 154 rectal, and 1, 045 urethral isolates was 30%, 17%, 29%, and 46%, respectively. Among contacts to GC, endocervical culture positivity was 6/26 (23%), pharyngeal 79/752 (11%), rectal 88/549 (16%), and urethral 71/445 (16%). Urethral culture positivity in male contacts without urethral discharge was low (6/221 [3%]). Pharyngeal culture positivity among GC contacts who were men who have sex with men was similar to heterosexual men (10% of 719 vs 12% of 17, p=0.68) but lower than pharyngeal positivity among women (43% of 14, p<0.01). Among patients with a recent NAAT+ screening test, cultures were positive in 12/35 (34%) endocervical, 133/514 (26%) pharyngeal, 168/337 (50%) rectal, and 30/94 (32%) urethral specimens. Most (91% of 476) men with urethritis and intracellular diplococci on gram stain were culture positive. Conclusion: Men with symptomatic urethritis had the highest GC culture yield (91%), followed by persons with recent GC NAAT+ (26–50%). Cultures in GC contacts had a modest yield (11%–23%). These criteria were appropriate for obtaining GC isolates for antimicrobial surveillance. Disclosure: No significant relationships.